Anti-CD20 therapy depletes activated myelin-specific CD8⁺ T cells in multiple sclerosis - Sabatino, Joseph J.; Wilson, Michael R.; Calabresi, Peter A.; Hauser, Stephen L.; Schneck, Jonathan P.; Zamvil, Scott S. (Proceedings of the National Academy of Sciences - PNAS, 2019)
CD8⁺ T cells are believed to play an important role in multiple sclerosis (MS), yet their role in MS pathogenesis remains poorly defined. Although myelin proteins are considered potential autoantigenic targets, prior studies of myelin-reactive CD8⁺ T cells in MS have relied on in vitro stimulation, thereby limiting accurate measurement of their ex vivo precursor frequencies and phenotypes. Peptide:MHC I tetramers were used to identify and validate 5 myelin CD8⁺ T cell epitopes, including 2 newly described determinants in humans. The validated tetramers were used to measure the ex vivo precursor frequencies and phenotypes of myelin-specific CD8⁺ T cells in the peripheral blood of untreated MS patients and HLA allele-matched healthy controls. In parallel, CD8⁺ T cell responses against immunodominant influenza epitopes were also measured. There were no differences in ex vivo frequencies of tetramer-positive myelin-specific CD8⁺ T cells between MS patients and control subjects. An increased proportion of myelin-specific CD8⁺ T cells in MS patients exhibited a memory phenotype and expressed CD20 compared to control subjects, while there were no phenotypic differences observed among influenza-specific CD8⁺ T cells. Longitudinal assessments were also measured in a subset of MS patients subsequently treated with anti-CD20 monoclonal antibody therapy. The proportion of memory and CD20⁺ CD8⁺ T cells specific for certain myelin but not influenza epitopes was significantly reduced following anti-CD20 treatment. This study, representing a characterization of unmanipulated myelin-reactive CD8⁺ T cells in MS, indicates these cells may be attractive targets in MS therapy.